The O-GlcNAc modification: three-dimensional structure, enzymology and the development of selective inhibitors to probe disease. (24th September 2010) - Davies, Gideon J.; Martinez-Fleites, Carlos
Abstract : Carbohydrates, their structures and the enzymes responsible for their synthesis and degradation, offer numerous possibilities for the design and application of probes with which to study and treat disease. The intracellular dynamic O-GlcNAc (O-linked β- N -acetylglucosamine) modification is one such glycosylation with considerable medical interest, reflecting its implication in diseases such as Type 2 diabetes and neurodegeneration. In the present paper, we review recent structural and mechanistic studies into the enzymes responsible for this modification, highlighting how mechanism-inspired small-molecule probes may be applied to study potential disease processes. Such studies have questioned a causal link between O-GlcNAc and Type 2 diabetes, but do offer potential for the study, and perhaps the treatment, of tauopathies.